Observation of dust particles ejected from the tungsten surface by transient heat flux with small-angle scattering of cw laser light - L.N. Vyacheslavov (Nuclear Materials and Energy, 2017)
A new test facility for experimental simulation of transient heat load expected in the ITER divertor during unmitigated events is developed. Application of a long-pulse (0.1–0.3ms) wide-aperture (up to 2cm2) electron beam as a heating device provides powerful energy loads at a tungsten target with FHF> 250MJm−2s−0.5. Dynamics of tungsten particles in the ablation plume is investigated with a novel for PSI experiments small-angle laser light scattering technique. The threshold of intense droplet generation and dynamics of particles sizes are estimated.